2007
DOI: 10.1172/jci30555
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and immunology of the cholinergic antiinflammatory pathway

Abstract: Cytokine production by the immune system contributes importantly to both health and disease. The nervous system, via an inflammatory reflex of the vagus nerve, can inhibit cytokine release and thereby prevent tissue injury and death. The efferent neural signaling pathway is termed the cholinergic antiinflammatory pathway. Cholinergic agonists inhibit cytokine synthesis and protect against cytokine-mediated diseases. Stimulation of the vagus nerve prevents the damaging effects of cytokine release in experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
1,167
5
49

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,389 publications
(1,251 citation statements)
references
References 98 publications
(125 reference statements)
30
1,167
5
49
Order By: Relevance
“…Present results in control lambs are similar to our previous results, showing a higher frequency of both isolated NNS and NNS bursts during AS (Duvareille et al, 2013;2007;Reix et al, 2003;Samson et al, 2005). Studies from our group have also shown that certain conditions can alter NNS frequency in lambs.…”
Section: Nns Frequencysupporting
confidence: 91%
“…Present results in control lambs are similar to our previous results, showing a higher frequency of both isolated NNS and NNS bursts during AS (Duvareille et al, 2013;2007;Reix et al, 2003;Samson et al, 2005). Studies from our group have also shown that certain conditions can alter NNS frequency in lambs.…”
Section: Nns Frequencysupporting
confidence: 91%
“…Eliciting the CAP by vagal electrical stimulation has been reported to have a protective role against fatal ventricular arrhythmia in myocardial ischemia/reperfusion animal models,10, 11 and vagal electrical stimulation also improves chronic heart failure in rats by increasing survival rate in long‐term myocardial infarction 12. It is well established that the beneficial effects of the CAP are mediated by acetylcholine receptors 13, 14. In addition, the α7‐nicotinic acetylcholine receptor (α7‐nAChR) subunit, which plays a crucial role in CAP, is expressed widely on the surface of inflammatory cells, and it significantly influences the anti‐inflammatory effect of the vagus nerve 15…”
Section: Introductionmentioning
confidence: 99%
“…In studies of experimental endotoxemia in rats, surgical dissection of the vagus nerve led to enhanced systemic TNF-production and accelerated the development of shock. In turn, electrical stimulation of the vagus nerve downregulated TNF-production and protected the animals from hypotension [24].…”
Section: Vagus Nerve and The Nicotinic Anti-inflammatory Pathwaymentioning
confidence: 95%
“…This cranial nerve that innervates most of the peripheral organs can downregulate inflammation by decreasing the release of TNF-, IL-1, IL-6, and high-mobility group box (HMGB) 1 protein by LPS-stimulated macrophages [24]. This antiinflammatory effect is mediated by an interaction between acetylcholine, the principal neurotransmitter of the vagus nerve, and the 7-nicotinic acetylcholine receptors on macrophages [24,25]. In studies of experimental endotoxemia in rats, surgical dissection of the vagus nerve led to enhanced systemic TNF-production and accelerated the development of shock.…”
Section: Vagus Nerve and The Nicotinic Anti-inflammatory Pathwaymentioning
confidence: 99%